2022
DOI: 10.1186/s40537-022-00627-x
|View full text |Cite
|
Sign up to set email alerts
|

Social media analysis of car parking behavior using similarity based clustering

Abstract: This paper investigates car parking users’ behaviors from social media perspective using social network based analysis of online communities revealed by mining the associated hashtags in Twitter. We propose a new interpretable community detection approach for mapping user’s car parking behavior by combining Clique, K-core and Girvan–Newman community detection algorithms together with a content-based analysis that exploits polarity, relative frequency and dominant topics. Twitter API was used to collect relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Using clustering methods, spatio-temporal parking patterns can also be found in other cities such as Seattle [50], Munich [41], and Beijing [51]. Even multiple parking behaviors around the globe can be identified through social media [52]. In general, these studies' results are consistent with our results.…”
Section: Dimension Reduction and Clusteringsupporting
confidence: 89%
“…Using clustering methods, spatio-temporal parking patterns can also be found in other cities such as Seattle [50], Munich [41], and Beijing [51]. Even multiple parking behaviors around the globe can be identified through social media [52]. In general, these studies' results are consistent with our results.…”
Section: Dimension Reduction and Clusteringsupporting
confidence: 89%
“…These methods aim to detect the underlying structure in the network, identify nodes with strong connectivity, and assign them to different communities or groups. Some wellknown community discovery algorithms, such as Louvain algorithm [18], GN algorithm [19] and modular maximization [20]and so on, have been widely used in social networks, news networks and other fields to help reveal community structures and social relationships.…”
Section: Related Workmentioning
confidence: 99%
“…The problems of parking behavior of residents have been studied by many researchers such as Arhab [11], Herath [12] and Kang [13]. For example, Elisabeth Fokker et al [14] investigated the short-term and long-term impact of a new subway line on parking behavior of residents and they found that in the short term, more commuters tend to park in the city center close to the stations of this public transport line.…”
Section: Literature Reviewmentioning
confidence: 99%